2018
DOI: 10.5194/bg-15-4923-2018
|View full text |Cite
|
Sign up to set email alerts
|

Colony formation in <i>Phaeocystis antarctica</i>: connecting molecular mechanisms with iron biogeochemistry

Abstract: Abstract. Phaeocystis antarctica is an important phytoplankter of the Ross Sea where it dominates the early season bloom after sea ice retreat and is a major contributor to carbon export. The factors that influence Phaeocystis colony formation and the resultant Ross Sea bloom initiation have been of great scientific interest, yet there is little known about the underlying mechanisms responsible for these phenomena. Here, we present laboratory and field studies on Phaeocystis antarctica grown under multiple iro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 91 publications
6
64
1
Order By: Relevance
“…Protein yield was determined using the BioRad DC Protein Assay. Protein digestion was performed using a modified tube gel method according to Bender et al, 2018. Briefly, protein was reduced, alkylated and digested with a 1:20 trypsin: protein ratio.…”
Section: Global Proteomic Approachmentioning
confidence: 99%
“…Protein yield was determined using the BioRad DC Protein Assay. Protein digestion was performed using a modified tube gel method according to Bender et al, 2018. Briefly, protein was reduced, alkylated and digested with a 1:20 trypsin: protein ratio.…”
Section: Global Proteomic Approachmentioning
confidence: 99%
“…, Bender et al. ). A few molecular markers, suggested to play a role in the formation of the extracellular colonial matrix and in cell aggregation (Bender et al.…”
Section: Discussionmentioning
confidence: 99%
“…), whereas iron addition was reported to increase growth rates and trigger colony formation in P. antarctica (Bender et al. ). In situ iron fertilization experiments in the SO reported haptophytes ( P. antarctica) among the groups contributing to the elevation in chlorophyll a signal after iron enrichment (Gall et al.…”
mentioning
confidence: 99%
“…Focal adhesion proteins connect cells to extracellular matrices both literally and figuratively, by holding cells in place and by initiating cellular responses to external conditions (Wozniak et al 2004). Likewise, Bender et al (2018) found genes for focal adhesion proteins, specifically glycoproteins, upregulated in colonial Phaeocystis antarctica. It is therefore likely that these proteins have an important function in structurally maintaining cell positions in the colonial matrix and signaling between colonial cells.…”
Section: Signaling Pathways Associated With Colony Formationmentioning
confidence: 99%